Individual doses for super cohort members exposed to atmospheric radioiodine from the Mayak releases with an emphasis on prenatal doses. (June 2020) - Eslinger, Paul W.; Degteva, Marina O.; Napier, Bruce A.; Tolstykh, Evgenia I.; Tokareva, Elena E.
Abstract: Time-dependent thyroid doses were reconstructed for 45, 837 members of the Southern Urals Population Exposed to Radiation Cohort (SUPER-C) living in the region around the Mayak Production Association facilities in Russia from 131 I released to the atmosphere from all relevant exposure pathways. The dose calculations are implemented in a Monte Carlo framework that produces best estimates and stochastic realizations of dose time-histories. The arithmetic mean thyroid dose from 131 I for SUPER-C members was 195 mGy; the median was 61 mGy. Overall, 131 I-thyroid doses for about 3.6% of SUPER-C members were larger than 1 Gy. For children born in 1940–1950, the dose was about 10% higher than in previous studies because doses during the prenatal period for 9, 117 individuals are included in the current work. Half of the individuals born in the region in 1950–1960 who remained in the study domain through 1972 received 9.4% or more of their total dose during the prenatal period. SUPER-C members residing in areas contaminated by discharges of liquid radioactive releases into the Techa River or the Kyshtym Accident in 1957 received 80% of their thyroid dose from airborne 131 I emissions. Highlights: Thyroid doses from airborne 131 I are reconstructed for 46000 members of the SUPER-C. Dose estimates during the prenatal period are included for those exposed in utero. The arithmetic mean 131 I-thyroid dose was 195 mGy and the median was 61 mGy. 131 I gave 80% of thyroid dose in areas with liquid wastes or the Kyshtym Accident . The thyroid dose estimates can be used for epidemiology studies.